Análisis de una red de distribución neumática para el cálculo de la potencia de un compresor de velocidad variable, con motor de reluctancia variable y variador de frecuencia - Mendieta Bajaña, Víctor Alfonso (2019)
The present project of analysis of the feasibility of a pneumatic distribution network for the calculation of the power of a variable speed compressor with variable reluctance motor and frequency variator is based on the information gathering of a company dedicated to food production with 7 process lines, it is based on the calculations on the load volume and simultaneity factor of a pneumatic network, in order to achieve a more efficient design for the energy saving of a compressed air compressor controlled through a proactive interface and easy to interpret. The methodology applied is quantitative, qualitative and experimental, with techniques of field observation, review and monitoring of pneumatic network systems and documentary review of international regulations; as well as the calculation of energy consumption of the plant at its minimum and maximum pressures. Using office tools, tools to measure the quality of energy and emissions to the environment. It was concluded with a cost-benefit analysis that showed a significant saving in dollars and how attractive the project of transition from a piston compressor to a screw compressor represents for the food industry, the low emission of gases and chemical pollutants, low maintenance costs, low noise level, technical economic analysis and the preponderant advantage of the proposed equipment.